Analysis of the Effect of the S.C.C.O.R.E Model in Detecting Potential Fraud in Financial Statements Through the Beneish M-Score Approach - Sanja Agata; Retno Yuni Nur Susilowati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the key factors within the S.C.C.O.R.E model (stimulus, capability, collusion, opportunity, rationalization, ego), widely known as the Fraud Hexagon framework, in detecting the potential for financial statement fraud using the Beneish M-Score approach. The stimulus element is proxied by financial instability, capability by change in director, collusion by cooperation with government project, opportunity by ineffective monitoring, rationalization by change in auditor, and ego by the frequent number of CEO’s pictures. This research focuses on companies that received the special E notation (companies with negative equity) listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period, with a total of 145 observations. The sample was selected using a purposive sampling technique. A quantitative approach is employed in this study, utilizing secondary data sourced from annual reports and financial statements, analyzed through logistic regression. The results show that financial instability, change in auditor, and frequent number of CEO’s pictures have a positive and significant effect on the potential for financial statement fraud. Meanwhile, change in director, cooperation with government project, and ineffective monitoring have no significant influence on the potential for financial statement fraud.